E-Surveilans Bloodstream Infection pada Pasien di Nitipuran Health Centre - Nungky Kescandra; Elsye Maria Rosa; Sri Sundari (Universitas Batanghari Jambi, 2020)
Infectious disease is still one of the health problems in the world, including Indonesia. The purpose of this study was to determine the occurrence of Bloodstream Infection using e-surveillance at Nitipuran Health Center. This study uses a mixed method with the Cohort Study approach. Research subjects were patient who did hemodialysis for quantitative data and doctors, nurses and head nurses for qualitative data. Quantitative data analysis with descriptive analysis, and qualitative analysis with in-depth interviews. Result: Four cases of Bloodstream Infection were identified using e-surveillance in NHC. And 4 cases is positive containing bacteria. Factors affecting Bloodstream Infection at the Nitipuran Hemodialysis Clinic are the awareness of medical personnel to keep personal hygiene still lacking and the compliance of medical personnel to perform SOP PPI is still low. Conclusion: Prevention of Bloodstream Infection in NHC needs to be improved by socialization on SOP for Prevention and Infection Control (PPI), forming a special team that is tasked with supervising the running of PPI SOPs and familiarizing themselves with maintaining hand hygiene.